Pergeseran Prioritas Regional Rusia terhadap Ukraina dalam Foreign Policy Concept Rusia Tahun 2013 - Rosalina, Gazella (Global and Policy Journal of International Relations, 2014)
ABSTRACTThis research examines the shift regional priority Russia to Ukraine in Foreign Policy ConceptRussia in 2013. Based on facts a shift in Foreign Policy Concept Russia in 2008 that befokus inCIS (Commonwealth of Independent States) shift in Ukraine as a top priority blocs in ForeignPolicy Concept Russia in 2013 brought up the question why Russia made Ukraine as prioritysectors in blocs. These problems later examined based on national interests, the concept causaltheory and geopolitical Eurasianisme, the concept Geo-economic and International EconomicCooperation to find the answer while the three Russian interests to Ukraine and politicalinterests, security interests and financial interests are headed for a European Union to theestablishment Eurasia. While there is an answer in research explanative - qualitative researchis not only proved but to become the basis in data collection to answer the variablescorrelation there. Through analysis of the review process bilateral relations between the twocountries in the European Union and establish the Eurasia for 10 years (in 2004 earlier in theyear 2013 can be concluded that Russian interests to Ukraine in politics to restore the SovietUnion as of Great Power through the establishment European Union Eurasia; economy fordomestic economic interests and strengthening regional economic integration Russia -European Union Eurasia and control economy to Ukraine; and in security, as buffer zoneRussia and controls the region.Keywords: European Union Eurasia, Russia, Ukraine, Foreign Policy Concept Russia in2013, Economic interests, political interests, Security interestsDOI:https://doi.org/10.33005/jgp.v2i02.2065